(untitled) (Fiep Bulletin - online, 2013)
The objective of this study was to present the main pedagogic approaches that guide the Brazilian Physical Education, using its principal authors, studies, theories, themes and methodological and ideological contexts. The Physical Education, as a curricular component, was seen as a way to prepare the youth for nation defense, to make the worker stronger or to stimulate new sport talents. The fact that the PE was considered as mere activity, sometimes relegated to a not really important status among the curricular disciplines, culminates in having to execute trendy tasks or national manias. Nowadays, its recognition as a curricular component by the 1996 state frameworks (LDB law # 9.394/96) evidences its essential contribution, that is to integrate itself with the others school disciplines. It also reinforces the need that the Physical Education has to relate itself in an interdisciplinary way with the other areas of the school knowledge. It is known that the Pedagogic Approaches are grouped by Macro Conceptions. The first group, related to the Humane Movement, is formed by the Constructivist, Psychomotor and Systemic Approaches. The second group is bigger and consists of Open Classes Approach; Critical-Overcomer; Plural Education; Critical-Emancipatory and Humanist, identified with the Body Movement Culture. In the third group is the Physical Aptitude Approach; Developmentalist and Technical which are related to Athletic Physical Education. It is important to enlighten the many possibilities that the physical education area can present for the teachers to work in the school (and other places) with different views, increased possibilities and specific actuation. Attending not only the students wishes, but also offering them a way that has not been followed by the physical education and sport pedagogies yet, it demonstrates, nowadays, a possible kind of actuation.